Rethinking Halal Tourism: What Truly Drives Revisits to Aceh-Sabang - Juli Dwina Puspita Sari; Rifyal Dahlawy Chalil (FEBI IAIN Langsa, 2026)
Halal tourism has emerged as a significant sector in the global tourism industry, prompting the Indonesian government to designate ten provinces, including Sabang-Aceh, as leading halal tourism destinations. Although strategic implementation is evident, research on factors influencing the revisit intention of international tourists remains limited. This study analyzes the influence of Social Media Marketing (SMM) and Islamic Attributes (IA) on Revisit Intention (RI), with Tourist Satisfaction (CS) as a mediating variable. A quantitative approach was employed through a survey of 100 international tourists visiting Aceh for recreation, selected using purposive sampling. Regression analysis indicates that SMM has a positive and significant effect on RI, with CS fully mediating this relationship. Regarding Islamic attributes, the direct effect of IA on RI was not significant. However, the indirect effect of IA on RI through CS was proven significant, confirming that CS acts as a full mediator in this relationship. These findings underscore the crucial role of tourist satisfaction in activating Islamic attributes to enhance revisit intention among international tourists in Aceh, regardless of their religious background. This study concludes that while Islamic attributes form the foundation of the destination, their influence on encouraging repeat visits is highly dependent on the comprehensive satisfaction experience perceived by visitors. For destination managers, it is advisable to prioritize holistic satisfaction through effective social media marketing and ensure that Islamic attributes contribute positively to the tourist experience. This approach can strengthen Aceh's position in the competitive global halal tourism market by attracting both Muslim and non-Muslim tourists.